2021
DOI: 10.1186/s13244-021-01136-w
|View full text |Cite
|
Sign up to set email alerts
|

Does lateral arm technique decrease the rate of clip migration in stereotactic and tomosynthesis-guided biopsies?

Abstract: Background Mammography-guided vacuum-assisted biopsies (MGVAB) can be done with stereotaxis or digital breast tomosynthesis guidance. Both methods can be performed with a conventional (CBA) or a lateral arm biopsy approach (LABA). Marker clip migration is relatively frequent in MGVAB (up to 44%), which in cases requiring surgery carries a risk of positive margins and re-excision. We aimed to compare the rates of clip migration and hematoma formation between the CBA and LABA techniques of prone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…Our findings compare similarly to prior studies that indicate LANA is safe and effective for normal and thinly compressed breast tissue. [2][3][4][5][6] We found no major complications, and the thinnest breast in our study compressed to 1.3 cm (compared with 2.9 cm for VNA). Weaver et al 5 observed no significant difference between LANA and VNA for bleeding or clip migration, again consistent with our findings.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…Our findings compare similarly to prior studies that indicate LANA is safe and effective for normal and thinly compressed breast tissue. [2][3][4][5][6] We found no major complications, and the thinnest breast in our study compressed to 1.3 cm (compared with 2.9 cm for VNA). Weaver et al 5 observed no significant difference between LANA and VNA for bleeding or clip migration, again consistent with our findings.…”
Section: Discussionsupporting
confidence: 43%
“…[2][3][4][5][6] We found no major complications, and the thinnest breast in our study compressed to 1.3 cm (compared with 2.9 cm for VNA). Weaver et al 5 observed no significant difference between LANA and VNA for bleeding or clip migration, again consistent with our findings. Kerger et al 2 reported faster procedures and increased patient throughput with LANA, though we noted identical total procedure times for LANA and VNA (both 16 minutes, P = .96).…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…Tissue marker placement after percutaneous breast biopsy is commonly used to enable accurate localization of lesions before surgery [1,2]. Several studies have shown that clip migration after stereotactic vacuum-assisted biopsy (SVAB), de ned as > 10mm displacement away from the biopsy cavity, is not rare [3][4][5][6][7][8][9][10]. Most cases of tissue marker displacement are believed to be caused by the "accordion effect", which is movement of the marker along the needle track immediately after the breast is decompressed [1,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%